EDUCATION OF DEVELOPMENT OF HEARING ABILITY AND PRONUNCIATION TRAINING OF CHILDREN WITH HEARING DEFECTS - Rakhimova Munirakhan Ilhomovna; Muhammadaliyeva Dilobar (Galaxy International Interdisciplinary Research Journal, 2023)
This article describes the auditory perception of children with hearing impairment, hearing aids, the program "Development of hearing and pronunciation training" and the development of auditory perception in PAT classes.